Analisis Penyebab Penundaan Klaim BPJS Kesehatan Pasien Rawat Inap di Rumah Sakit X - Setiawan, Akbar Pratama; Setiatin, Sali; Nuraeni, Yayang Ayu (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
Although digitalization through the Hospital Management Information System (SIMRS) has been implemented, integration with BPJS’s e-claim system remains suboptimal, leaving certain processes manual and prone to errors. Previous studies have identified common causes of pending claims, including incomplete medical documentation and coding errors. However, there is still limited research examining how internal factors—such as staff competency, inter-unit coordination, and the effectiveness of SOPs—interact with external factors like BPJS regulatory changes and system integration challenges. In particular, few studies have focused on RSUP Dr. Hasan Sadikin to explore why pending claims persist despite ongoing digitalization efforts. Therefore, this study aims to conduct an in-depth analysis of the factors causing delays in BPJS Health claims for inpatients at RSUP Dr. Hasan Sadikin Bandung and to propose strategic recommendations to minimize such delays in the future. Using a qualitative approach with a case study method, data were collected through in-depth interviews and document reviews involving administrative staff, claim verifiers, and hospital management. The findings show that delays are mainly caused by mismatches between medical and administrative documents, late data entry by officers, and technical issues in the claim submission system. In addition, insufficient understanding of BPJS procedures and poor coordination between departments also contribute to the problem. To overcome these challenges, the hospital must improve its internal workflow, provide regular staff training, and upgrade its information systems. The results of this study are expected to serve as a reference for hospitals in managing BPJS claims more effectively and ensuring timely service reimbursement.